THE EFFECT OF FOREIGN INVESTMENT, GOVERNMENT EXTERNAL DEBT, AND GOVERNMENT EXPENDITURE ON GROSS DOMESTIC PRODUCT IN INDONESIA - Ira Sukma; Khairil Anwar (Journal of Malikussaleh Public Economics, 2021)
This study aims to determine the influence of foreign investment, foreign debt, and government spending on Gross Domestic Product in Indonesia during 2005-2019. The data analysis method used in this study is a multiple regression analysis models using the Eviews application. The results show partially (t-test) show that foreign investment, foreign debt, and government expenditure have a positive and significant effect on gross domestic product.Then, the correlation coefficient or R-Squared value is 0.736793 or 73.67%. It shows that there is a strong correlation between the independent variables and the dependent variable. It concludes that foreign investment, foreign debt, and government spending have a positive and significant effect on the provincial gross domestic product in Indonesia from 2005 to 2019.